Effect of H2O2 Addition on the Photocatalyst Properties of Ag3PO4 for Methylene Blue Photodegradation - Febiyanto Febiyanto; Muhammad Sofi Khoerul Amal (Walisongo Journal of Chemistry, 2021)
In this work, a facile enhanced property of Ag3PO4 photocatalyst using H2O2 for methylene blue photodegradation has been conducted. Ag3PO4 photocatalyst was synthesized using the co-precipitation method. Then, the photocatalytic activity and stability of Ag3PO4 were tested in the methylene blue degradation under the addition of an H2O2 30% solution. According to the results, the prolonged photocatalysis reaction led to a decrease in the catalysis ability of the Ag3PO4 photocatalyst. Meanwhile, the addition of 5 mL of H2O2 (AH-10% sample) tends to enhance the stability of Ag3PO4 photocatalyst with the dye removal percentage and recycling test were up to 90.3% and three recycle runs, respectively. The low stability of Ag3PO4 might be due to the catalyst photo-corrosion through Ag+ reduction. This research suggests that H2O2 is beneficial to inhibit the photo-corrosion of Ag3PO4 photocatalyst, even though released Ag ions that were caused by the excess addition of H2O2 oxidizing agent should be considered.